Circadian rhythms in bacterial sepsis pathology : what we know and what we should know - Mul Fedele, Malena Lis (2021)
Fil: Mul Fedele, Malena Lis. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas. Laboratorio de Cronofisiología; Argentina